John Dryden's Poetry of Death - Tabrizi, Taghipour Pouria (My University, 2008)
In this project, I explore John Dryden's scepticism about the possibility of encomium, lamentation, and consolation in his poetry of death. Drawing on close readings of individual poems, comparisons of each work with its literary precedents, and examinations of the poet's artistic ideals as expressed in his prose, I trace Dryden's development of a language of poetic commemoration that is individualistic, anticonciliatory and anti-elegiac. The first two chapters focus on Dryden's attempts to reconcile ethical and social functions of the panegyric genre with his deep respect for the deceased individual and her grieving family members. The third chapter examines two short elegies in which Dryden bestows upon the public moumer a humanness missing from conventional elegies and mortuary rituals, and questions whether communal expressions of lament are able to capture the private feelings of individuals.
Keywords: English and Cultural Studies; English Language and Literature; English Language and Literature